Stability of target irradiation for high-repetition rate direct-drive facilities - Schiavi Angelo; Atzeni Stefano; Marocchino Alberto (EPJ Web of Conferences, 2013)
The illumination of a spherical target for Inertial Confinement Fusion is studied in the direct-drive approach. Three main sources of laser parameter fluctuation are taken into account, and a statistical analysis of the illumination configuration has been carried out in order to assess the stability of the illumination, and the shot-to-shot fluctuation of the laser intensity pattern.